Transnational Social Workers: Making the Profession a Transnational Professional Space. (18th July 2012) - Bartley, Allen; Beddoe, Liz; Fouché, Christa; Harington, Phil
Abstract : This paper draws on research conducted in New Zealand from 2009 to 2011 with overseas-qualified social workers as members of a global profession experiencing both great international demand for their skills and unparalleled flows of professional transnationalism. In line with the international social work literature, this cohort of migrant professionals offers a range of needed skill and expertise as well as unique challenges to local employers, client communities, and the social work profession as a whole. With a specific focus on mixed-methods data dealing with participants' induction experiences and engagement with professional bodies, this paper argues that migrant social workers have created in New Zealand a transnational professional space that demands a response from local social work stakeholders.